Socio-legal research must be and can be global. And you are part of it - Guibentif, P. (IISL International Master's in Sociology of Law - Extracurricular Lecture, 2024)
About the importance of developing a truly international socio-legal research, about the role in this domain of the International Institute for the Sociology of Law (IISL), and of the Research Committee on Sociology of Law of the International Sociological Association, one of the two founders of the Institute, and about the necessary individual contributions to this effort of internationalisation, including the contributions of the students of the IISL Master’s Programme themselves, through the interaction between during the courses and through the research they will start during the Master’s Programme.